2011
DOI: 10.1007/s00432-011-1008-y
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome of patients with liver-only metastases from breast cancer after mastectomy: a retrospective analysis

Abstract: The combined treatment of TACE and systemic chemotherapy may prolong survival for liver metastases in breast cancer after mastectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…In one study with a high percentage of these patients up to 33% recurrence of liver metastasis was stated [26]. The above-mentioned problem with inhomogeneous and small study populations progresses further when taking alternative treatments such as transarterial chemoembolisation and radiofrequency ablation into account [4648]. …”
Section: Discussionmentioning
confidence: 99%
“…In one study with a high percentage of these patients up to 33% recurrence of liver metastasis was stated [26]. The above-mentioned problem with inhomogeneous and small study populations progresses further when taking alternative treatments such as transarterial chemoembolisation and radiofrequency ablation into account [4648]. …”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study by Duan et al reported a 1-year survival rate of 76.2% in those treated with cTACE combined with systemic chemotherapy compared to 48.1% in those treated with systemic therapy alone (p ¼ 0.027). 108 In a similar retrospective review comparing cTACE and systemic chemotherapy with chemotherapy alone, Li et al also showed a survival benefit with combined therapy (63 vs. 33.9%). 109 Data relating to the use of DEBDOX are limited.…”
Section: Thermal Ablation Of Metastatic Breast Cancermentioning
confidence: 94%
“…With surgery, the OS rate is 49-75/41-61% at 3/5 years, respectively, with a median of 3.8-5.3 years (20-24). With TACE, the OS rate was 63-76/13-48% at 1/3 years, respectively (25)(26)(27) (Table II). Although severe adverse effects are rare, Caralt et al reported that 2/12 patients (17%) suffered from bile leakage postoperatively (28).…”
Section: Discussionmentioning
confidence: 99%